1992
DOI: 10.1128/mcb.12.2.518
|View full text |Cite
|
Sign up to set email alerts
|

Fetal liver pro-B and pre-B lymphocyte clones: expression of lymphoid-specific genes, surface markers, growth requirements, colonization of the bone marrow, and generation of B lymphocytes in vivo and in vitro.

Abstract: We describe here the development and characterization of the FLS4.1 stromal line derived from 15-day fetal liver of BALB/c embryos and defined culture conditions that efficiently support the cloning and long-term growth of nontransformed B-220+ 14-day fetal liver cells at two stages of B-cell development, namely, pro-B lymphocytes (immunoglobulin [Ig] genes in germ line configuration) and pre-B cells (JH-rearranged genes with both light-chain Ig genes in the germ line state). All B-cell precursor clones requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
(52 reference statements)
1
32
0
Order By: Relevance
“…3 and data not shown). We have previously found that FLS4.1 stromal cells, although able to support development and growth of fetal liver pre-B cells, are unable to support differentiation of pre-B cells into surface IgM+ B lymphocytes (12). Therefore, the lack of IgM+ B lymphocytes in the yolk sac cells cultured on FLS4.1 stromal cells was not unexpected.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…3 and data not shown). We have previously found that FLS4.1 stromal cells, although able to support development and growth of fetal liver pre-B cells, are unable to support differentiation of pre-B cells into surface IgM+ B lymphocytes (12). Therefore, the lack of IgM+ B lymphocytes in the yolk sac cells cultured on FLS4.1 stromal cells was not unexpected.…”
mentioning
confidence: 90%
“…Cells from the first culture (Fig. 1 (12) (025% confluency) in six-well Costar plates in the presence of rIL3 (20 units/ml) (12), rIL6 (10-50 units/ml) (12), and rIL7 (500 units/ml) (12), in a final volume of 1.5 ml of culture medium (see above) at 37°C for 8-10 days. One milliliter of fresh culture medium containing rIL7 was added to each well at day 5-6 of culture.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse pro-B cells Ba\F3 [27] were engineered to express the IL-11 receptor complex. Experimental procedures have been described previously [28].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%